Catalisadores mesoporosos a base de nióbio modificados com níquel: um estudo sobre a atividade fotocatalítica e mecanismos de reação - Iza Fonte Boa e Silva (2017)
This work was based on the synthesis of a niobium (V) oxide with mesoporous structure and relatively high surface area for this type of material. The synthesis was performed according to the Evaporation Induced Self-Assembly method, followed by calcination. Afterwards, chemical modifications were introduced with nickel (II) oxide. Thus, four materials with different mole percentages of nickel in the structure were prepared being (i) 0, (ii) 1.0, (iii) 2.5 and (iv) 5.0 and characterized by techniques such as X-rays diffraction, surface area measurements and porosity, scanning electron microscopy, microanalysis by energy dispersive spectroscopy, temperature programmed reduction, zeta potential measurements and Raman and diffuse reflectance spectroscopies. The temperature used in the final calcination (400ºC) was chosen to maintain the maximum surface area in the materials, although its structure is predominantly amorphous. The increase for nickel reduced the surface area of the materials by closing some mesoporous, but did not cause significant structural change. There was also no change in bandgap (Eg) with the modification, showing that the materials were predominantly impregnated. The zero charge point of all materials appears to be at pH about 3 4. The increase in nickel amount, however, appears to increase the reducibility of Nb5+ species. The materials were tested in some advanced oxidation processes (AOPs) for methylene blue and indigo-carmine dyes. The reactions were accompanied by absorption in the UV-Vis region and analysed by ESI-MS. The results showed that photocatalysis led to the discoloration of about 80% and 100% of 40 ppm solutions of methylene blue and indigo-carmine, respectively, at pH 5. The material containing 1% nickel showed the most promising, with an apparent velocity constant (kap) of 0.022 min-1 and a half-life time of 32 minutes for the indigo-carmine solution. Analyses by ESI-MS showed that the dyes were in the process of degradation. Only 50 minutes were required for the discoloration of about 65% of a 300 ppm solution of methylene blue and 20 minutes for 100% of a 40 ppm solution of indigo-carmine by photo-Fenton like reactions. The results of ESI-MS and study of the mechanisms of photocatalytic reactions showed that the classical (indirect) mechanism seems to be the main one, being favoured by the modification with nickel. The materials could be activated by photosensitization through compounds capable of strongly adsorbing to them, but these reactions are slower.